Unstable states of In_xAl_yGa_1 - x -yN quaternary alloys - Díaz Albarrán, S.F.; Rodríguez Peralta, P. (Revista Mexicana de Física, 2010)
Regions of unstable states characterized by the spinodal decomposition of high-Al-content In_xAl_yGa_1 - x - yN quaternary alloys lattices matched to the GaN (001) substrate are described. The alloy are represented as strictly regular solutions. In the analysis we take into account the internal deformation and elastic strain energies. The regions of unstable states or ranges of spinodal decomposition considering the compositions 0.06 x 0.18 and 0 y 0.95 with and without elastic energy are demonstrated up to 580^°C. We conclude that high concentrations of aluminum dramatically increased the phase separation temperature.